Corn leaf disease detection using deep convolution neural network - Rabbi, Rawhatur; Arefin, Mohammad Yasin; Turna, Iffat Fahmida; Zannat, Zahra (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.